IDENTIFIKASI HAMBATAN PENGEMBANGAN SMA MUHMMADIYAH 3 SURAKARTA - Erna Widiyastuti; Mohamad Ali (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2021)
SMA Muhammadiyah 3 Surakarta is a private school organized by the PDM (Majelis Dikdasmen) Educational Council of Surakarta City. This study examines the outline of the development of students and the identification of barriers to development. The research location in SMA Muhammadiyah 3 Surakarta. Collecting data using the methods of observation, interviews, and documentation with descriptive analysis. The results showed that the outline of the development of students at SMA Muhammadiyah 3 Surakarta can be divided into 3 stages, namely the pioneering (1981/1982-1990/1991), the development (1991/1992-2001/2002), and the decline (2002/ 2003-2020/2021). Obstacles to the development of SMA Muhammadiyah 3 Surakarta come from management and organizer factors. From the school management side, namely; less responsive to problems; less use of SBM; lack of coordination, the absence of a school culture/school program that can attract public attention. As for the organizers (penyelenggara), namely: the Education Council (Majelis Dikdasmen) did not greet the administrators, the Education Council did not respond to the various problems that arose.